Dielectric spectroscopy studies of ZnO single crystal - 成鹏飞 李盛涛 王辉 (Chinese physics B, 2013)
Dielectric relaxation and charge transport induced by electron hopping in ZnO single crystal are measured by using a novocontrol broadband dielectric spectrometer. Typical Debye-like dielectric relaxation originating from electronic hopping between electronic traps and conductive band in surface Schottky barrier region is observed for ZnO single crystal-Au electrode system. However, after insulation of ZnO single crystal by heat treatment in rich oxygen atmosphere, dielectric relaxation and alternating current conductance are observed simultaneously in the dielectric spectra, implying that dielectric relaxation and charge transport can be induced simultaneously by electronic hopping at high temperature in an ordered system. The intrinsic correlation between local dielectric relaxation and long range charge transport offers us a new method to explore complicated dielectrics.